Psycho-Socio-Juridic Review Of Lockdown And Work From Home Policies On Psychological Symptoms In Productive Groups And Strategic Solutions Of National Economy - Yohanes Firmansyah; Imam Haryanto (Jayapangus Press, 2021)
Covid-19 pandemic has a significant impact on all strategic aspects of human life. The influential aspects are the health, economic and socio-cultural. The Covid-19 pandemic creates a dilemma for the Government to find the best way to benefit from various sectors efficiently. One of them is the implementation of lockdown and work from home to reduce the spread of Covid-19, but this has an impact on the emergence of various psychological disorders and the balance of the economic balance which tends to be negative. The focus of this research is to reveal the impact of the Covid-19 pandemic and lockdown and Work From Home policies on psychological symptoms and to find the best alternative solutions in terms of the economic sector. This research consists of 2 main parts, namely survey research and research that examines the problems based on sociology with qualitative methods with the type of normative juridical research. The results of this study reveal that during the Covid-19 pandemic period caused a 39.1% incidence of insomnia, 12.1% incidence of depression, and 26.3% incidence of anxiety from various levels. Still, there was no strong relationship and correlation between existing policies such as Work From Home, income, layoffs, spiritual, psychological symptoms. A literature review reveals the most effective way to bridge these three aspects (health, economy, and psychology) is by applying the form of shifting or taking turns by dividing into a minimum of 2 teams, namely a minimum of 14 days of work and a minimum of 14 days for independent isolation at home.